Old, sick, alone, and poor: A welfare analysis of old-age social insurance programs - R. Anton Braun; Karen A. Kopecky; Tatyana Koreshkova (Federal Reserve Bank of Atlanta, 2013)
Poor heath, large acute and long-term care medical expenses, and spousal death are significant drivers of impoverishment among retirees. We document these facts and build a rich, overlapping generations model that reproduces them. We use the model to assess the incentive and welfare effects of Social Security and means-tested social insurance programs such as Medicaid and food stamp programs, for the aged. We find that U.S. means-tested social insurance programs for retirees provide significant welfare benefits for all newborn. Moreover, when means-tested social insurance benefits are of the scale in the United States, all individuals would prefer to be born into an economy with no Social Security. Finally, we find that the benefits of increasing means-tested social insurance are small or negative, if we hold fixed Social Security contributions and benefits at their current levels.
Keywords: E62; H31; H52; H55; 330; Social Security; Medicaid; social insurance; elderly; medical expenses